The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1965
DOI: 10.1126/science.149.3681.295
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Communication: Renal, Urinary Bladder, Sensory, and Salivary Gland Cells

Abstract: In four epithelial cell systems (salivary gland, renal, urinary bladder, and sensory cells) cells are interconnected as far as much of their ion content is concerned. In the salivary gland and renal epithelia, all cells of the epithelium are interconnected; and communication between a given cell and any of its nearest neighbors is equally good. In the bladder and sensory epithelia, communication appears to be more restricted, manifesting itself in chains of connected cells in the former, and in small groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
2
1

Year Published

1966
1966
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(67 citation statements)
references
References 10 publications
2
62
2
1
Order By: Relevance
“…The mean coupling coefficient for the parotid cells (0.69 + 0.04) is higher than that reported in most other vertebrate epithelial systems (Gilula, Reeves & Steinbach, 1972;Johnson & Sheridan, 1971;Jamakosmanovic & Loewenstein, 1968;Loewenstein et al 1965). Only rat liver, in vitro, at 0*75-0*96 (Borek, Higashino & Loewenstein, 1969), Novikoff hepatoma, in vitro, at 0*9 (J. D. Sheridan & M. G. Hammer, unpublished observations), and pancreatic acinar cells (Petersen & Ueda, 1976) show higher values.…”
Section: Discussioncontrasting
confidence: 56%
“…The mean coupling coefficient for the parotid cells (0.69 + 0.04) is higher than that reported in most other vertebrate epithelial systems (Gilula, Reeves & Steinbach, 1972;Johnson & Sheridan, 1971;Jamakosmanovic & Loewenstein, 1968;Loewenstein et al 1965). Only rat liver, in vitro, at 0*75-0*96 (Borek, Higashino & Loewenstein, 1969), Novikoff hepatoma, in vitro, at 0*9 (J. D. Sheridan & M. G. Hammer, unpublished observations), and pancreatic acinar cells (Petersen & Ueda, 1976) show higher values.…”
Section: Discussioncontrasting
confidence: 56%
“…2 a illustrates an experiment in which an ion current is passed between the interior and exterior of a cell (I) of the rat liver surface, and the resulting resistive m e m b r a n e voltages are measured in this cell and simultaneously in an adjacent one (H). As in m a n y other types of epithelial cells (12,17), the resistance of the surface m e m b r a n e of the liver cell is quite ohmic: the m e m b r a n e shows no sign of electrical excitation and little or no rectification to a wide range of current. Most striking is the small difference in resistive membrane voltage in the two cells.…”
Section: Lack Of Communication Between Cancer Cellsmentioning
confidence: 78%
“…It consisted essentially of injecting a current of ions into a cell and determining what fraction of the current passes into an adjacent cell. The method is readily applicable to many cell systems and provides quantitative information (9,13,17). Liver cells were used for the study.…”
Section: Introductionmentioning
confidence: 99%
“…references 10,11,14), certain alternatives should be mentioned. The existence of a high resistance barrier surrounding the whole blastodisc is excluded since virtually no potential changes were recorded unless both current and recording micropipettes were intracellular.…”
Section: Discussionmentioning
confidence: 99%
“…certain nerve cells, cardiac, and visceral muscle cells) (1,2,4,5), but also between certain nonexcitable cells (e.g. glial cells and epithelial cells in insects, amphibians, and mammals) (8)(9)(10)(11)13). In all the cases cited above, electron microscopy has shown that the cells are connected by regions of specialized membrane apposition (e.g.…”
Section: Introductionmentioning
confidence: 99%